2011
DOI: 10.5863/1551-6776-16.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Buprenorphine for Sublingual Use in Neonates

Abstract: OBJECTIVES The only medication used sublingually in the neonate is buprenorphine for the treatment of neonatal abstinence syndrome (NAS). Compared with morphine, buprenorphine reduces the length of treatment and length of hospitalization in neonates treated for NAS. The objective of this study was to characterize the stability of ethanolic buprenorphine for sublingual administration. METHODS Buprenorphine solution was prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This formulation is stable at room temperature for at least 30 days and at 7 days in polypropylene-dispensing syringes. 63 Additional advantages included microbiologic asepsis and simplicity of preparation in the context of a clinical trial. Ethanol does not decrease opioid withdrawal and is not expected to have provided any of the efficacy seen in NAS clinical trials.…”
Section: Formulationmentioning
confidence: 99%
“…This formulation is stable at room temperature for at least 30 days and at 7 days in polypropylene-dispensing syringes. 63 Additional advantages included microbiologic asepsis and simplicity of preparation in the context of a clinical trial. Ethanol does not decrease opioid withdrawal and is not expected to have provided any of the efficacy seen in NAS clinical trials.…”
Section: Formulationmentioning
confidence: 99%
“…Morphine, methadone and buprenorphine are all available as generic formulations and differences in the costs between drug acquisition or local compounding are negligible. The usual buprenorphine preparation contains 30% ethanol and is stable for 30 days when stored at room temperature [ 42 ]. Ideally, pediatric formulations should be free of ethanol, but when an ethanol free solution is not avaliable the American Academy of Pediatrics recommends that the blood ethanol concentrations not exceed 250 mg/L.…”
Section: Potential Role Of Buprenorphine In Pharmacologic Management Of Oud and Nowsmentioning
confidence: 99%
“…16 On the other hand, buprenorphine used in NOWS trials contains a high amount of alcohol, with one reported formulation containing 30% of ethanol. 17 Although there is an increasing number of clinical trials on the comparative efficacy of treatment agents in NOWS, here, we also draw attention to the importance of optimizing the dosing regimen, which can be arguably equally important at identifying the optimal treatment agent. Oftentimes, variations in starting doses, escalation/weaning schemes, and use of adjunctive therapy and nonpharmacological therapy may limit the generalizability of comparative efficacy study results to broader patient populations.…”
Section: Overview Of the Management Of Nowsmentioning
confidence: 99%
“… 16 On the other hand, buprenorphine used in NOWS trials contains a high amount of alcohol, with one reported formulation containing 30% of ethanol. 17 …”
Section: Overview Of the Management Of Nowsmentioning
confidence: 99%
See 1 more Smart Citation